A Lexicographic Approach to Teaching the English Article System: Help or Hindrance? - Kim, Sugene (Lexikos, 2018)
This article reports on changes in EFL learners' article choice performance before and after receiving lessons on the main rules applicable to article usage combined with dictionary consultation guidance. A sample of 43 Korean college students undertook the same forced-choice elicitation task once as a diagnostic test and again as a post-intervention test at three-month intervals. Unlike the diagnostic test, in which the participants were only asked to choose the correct articles, the post-intervention test asked them to give written accounts of their decision-making procedures as well. The analyses of the diagnostic test results, specifically the items requiring the indefinite article or the zero article, demonstrated EFL learners' struggle with indeterminate nominal numbers, underlining the importance of clear lexicographic treatment of such information. Further, the post-intervention test and the written think-aloud data analyses suggested that although using a bilingualised dictionary for nominal countability is useful in general, dictionary consultation can sometimes impede users from using articles correctly. Specific problem areas are discussed.